2019
DOI: 10.1590/fst.38517
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity and biochemical changes during production of Lentinula edodes (Berk.) Pegler

Abstract: Shiitake is an important edible and medicinal mushroom cultivated worldwide. Ots cultivation involves a complex process of browning that precedes the primordia initiation. The present work through the evaluation of enzymes, lectin and β-glucan during the cultivation cycle of Lentinula edodes, the degradation of cellulose, hemicellulose and lignin, attempted to correlate these with mushroom yield. Strains UFLA-LE1, UFLA-LE2 and UFLA-LE6 consumed significantly more hemicelluloses than the other three strains wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…For successful cultivation, the substrate must allow mycelial development in a short period and with vigor, because it is the phase with a high risk of contamination (Montini, 2001). In the studied substrates, the time to complete colonization ranged between 65 and 100 days (Tables 6 and 9), faster results than those obtained by Sousa et al (2019) out of 126 days and slower than those obtained by Atila (2019) from 32 to 46 days and Gao et al ( 2020) from 49 to 50 days; however, there are differences in formulations, compositions, raw materials, and lineages.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For successful cultivation, the substrate must allow mycelial development in a short period and with vigor, because it is the phase with a high risk of contamination (Montini, 2001). In the studied substrates, the time to complete colonization ranged between 65 and 100 days (Tables 6 and 9), faster results than those obtained by Sousa et al (2019) out of 126 days and slower than those obtained by Atila (2019) from 32 to 46 days and Gao et al ( 2020) from 49 to 50 days; however, there are differences in formulations, compositions, raw materials, and lineages.…”
Section: Discussionmentioning
confidence: 58%
“…The PR obtained in the experiments (Tables 8 and 11) was higher than the PR achieved by Sousa et al (2019) from 0.0 to 16.2%, they related to the higher yields obtained in substrates that had less cellulose degradation. Values are obtained in different formulations, compositions, and raw materials.…”
Section: /7mentioning
confidence: 71%
“…During mushroom cultivation, distinct stages of development and growth of the fungus are observed, with emphasis on mycelial growth (substrate colonization), browning process, primordium formation and development of the basidiocarp (the structure known as the mushroom), and these phases are directly affected by the concentrations of lignin, cellulose and nitrogen in the fungal growth substrate (Sousa et al, 2019). Associated with mushroom development, greater laccase activity is obtained during substrate colonization when compared to basidiocarp formation (Bellettini et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that intensity of browning can vary according to light, aeration and temperature [22,23]; the process is accelerated by oxygen and light exposition [24]. Some enzymatic activities are modified: enzymes related to light sensing (kinases and G proteins-coupled receptors), melanogenesis (tyrosinases) and cell wall degradation (glucanases, chitinases, laccases, manganese peroxidase and lignin peroxidase) [25,26]. The browning process develops a brown layer of mycelia which not only improves mushroom quality but also discourages mold contamination [27].…”
Section: Introductionmentioning
confidence: 99%